MULTI-PARTY SYSTEM AS A NECESSARY ELEMENT OF DEMOCRATIC STATEHOOD - Soliev Rustam Sultanmurodovich (TADQIQOTLAR, 2026)
Annotation: The article analyzes the role and significance of the multi-party system in the context of democratic reforms implemented in the new Uzbekistan. The author pays special attention to the issues of increasing the role of political parties in society, establishing a systematic dialogue with the electorate, and enhancing political culture. Furthermore, the article provides scientific and theoretical conclusions on improving the legal framework of political parties and strengthening their participation in state building.